Baguio by bike towards a vernacular intermedia mapping of place - Manuel, Fara Martia P.; Abaya, Leo Antontio (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
This thesis research focused on exploring intersections between the visual arts and geography by means of personal cartography. Its ultimate goal is to find a sense of belongingness in my new-found home, Baguio. For methodology, I used the positionality--artist-voyageuse (artist-traveler) whose vantage point reflects that of an outsider starting out as new resident of Baguio. The visual arts approach employed in this thesis research could be described as exploratory and experimental as it assesses mapping as an emergent practice by means of performing local spatial knowledge. In my mappings, I frame Baguio as a leisure city, a place for sentimental sojourns and as my new home. I begin by studying place representation and creative cartographic methods in probing the meaning of place, then I proceed to determining everyday life moments that mirrors how Baguio's spatial qualities contribute to my self-awareness. My exploratory method centered on how I am able to psychogeographically decipher locations, map them out and create a record of Baguio by asserting a mobile presence as a biker moving around the city. The study explored how as a biker, I take a synesthetic route around the city to trigger a dialogue between bodily interior and Baguio's landscape exterior. The culminating product is a collection of intermedia map art in the form of site-specific installation, sculptural assemblage and print--tokens that represent my personal vernacular approach in mapping Baguio.
Thesis (Master of Fine Arts)--University of the Philippines Diliman
Bibliography ; leaves 114-117.
Keywords: Art and geography -- Philippines